Comparison of circulation patterns of mumps virus in the Netherlands and Spain (2015–2020) - Gavilán, Ana M.; van de Nes-Reijnen, Linda; Castellanos, Ana; Woudenberg, Tom; López-Perea, Noemí; Masa-Calles, Josefa; Echevarría, Juan E.; Fernández-García, Aurora; Bodewes, Rogier (Frontiers in Microbiology, 2023)
Mumps is a viral infection characterized by inflammation of the parotid glands. Despite of vaccination programs, infections among fully vaccinated populations has been reported. World Health Organization (WHO) recommends molecular surveillance of mumps based on sequencing of the small hydrophobic (SH) gene. The use of hypervariable non-coding regions (NCR) as additional molecular markers has been proposed in multiple studies. Circulation of mumps virus (MuV) genotypes and variants in different European countries can be found in the literature. From 2010-2020, mumps outbreaks caused by genotype G have been described. However, this issue has not been analyzed from a wider geographical perspective. In the present study, sequence data from MuV detected in Spain and in The Netherlands in a period of five years (2015- march 2020) were analyzed to gain insights in the spatiotemporal spread of MuV at a larger geographical scale than in previous local studies. A total of 1121 SH and 262 NCR between the Matrix and Fusion protein genes (MF-NCR) sequences from both countries were included in this study. Analysis of SH revealed 106 different haplotypes (set of identical sequences). Of them, seven showing extensive circulation were considered variants. All seven were detected in both countries in coincident temporal periods. A single MF-NCR haplotype was detected in 156 sequences accounting by the 59.3% of total, and was shared by five of the seven SH variants, as well as three minor MF-NCR haplotypes. All SH variants and MF-NCR haplotypes shared by both countries were always detected first in Spain. Our results suggest a transmission way from south to north Europe. The higher incidence rate of mumps in Spain in spite of similar immunization coverage in both countries, could be associated with more risk of MuV exportation. In conclusion, the present study provided novel insights into the circulation of MuV variants and haplotypes beyond the borders of single countries. In fact, the use of MF-NCR molecular tool allows to reveal MuV transmission flows between The Netherlands and Spain. Similar studies including other (European) countries are needed to provide a wider scope to the data shown in the present study.